PERAN FUNGI Phanerochaete chrysosporium DALAM PROSES PRETREATMENT BAGASSE DAN TANDAN KOSONG KELAPA SAWIT MENJADI SUMBER ENERGI TERBARUKAN - Nuniek Hendrianie (Purifikasi, 2009)
Bagasse and oil palm empty fruit bunches are high cellulosic waste, which contain considerably high lignocellulosic compounds. Therefore, these waste can potentially be used as renewable energy source. This experimental work utilised bagasse and oil palm empty fruit bunches as raw material in biogas production. The reason of using this high cellulosic waste as raw material of biogas had a constraint in hydrolyses process. Therefore, cellulosic pretreatment should be carried out before biogas production process. A biological pretreatment using fungi is chosen, because it produces better result than other methods. The aim of this experiment is to investigate the performance of Phanerochaete chrysosporium on the pretreatment of bagasse and oil palm empty fruit bunches, and its effect on biogas qualities and quantities. The method used in this experimental work was divided into two steps, which were fungal pretreatment and biogas production. Bagasse waste was collected from a Sugar Plant (PT PG Tjandi), and oil palm empty fruit bunches was from PT Sajang Heulang Angsana Mini Factory. The wastes were grinded and added with a ratio of 1:8 of water - P. chrysosporium culture. Then it was innoculated in PDA for 7 days, and filled into culture medium of pH 8. This culture was homogenised until fungi concentration of 5 x 106 spore/ml. Waste sludge and fungi were filled into stirred and aerated pretreatment tank at a temperature range of 35-40°C, and pH value of 4-4.5 for 7 days. While fungal pretreatment was prepared, starter for biogas production process was made by mixing manure and water in a ratio of 1:2. This mixture was fermented for 5 days. Waste resulted from fungal pretreatment was mixed with starter and water in ratio of starter : waste : water as 1:2:4. Reactor temperature was kept constant at 30°C, with a fermentation period of 15 days. The best experimental result was reached at 20% fungi added. At this composition glucose concentration in oil palm empty fruit bunches reactor was 11.085%, from the initial glucose concentration of 5.78%. The cellulose content decreased from 71.68 to 41.35%. The best gas composition was 75.82% methane with heating value of 11248 kkal/kg. This composition was reached by 20% fungi added.